KARAKTERISASI SIFAT KIMIA TEPUNG KACANG LAWA MERAH (Phaseolus vulgaris L.) DENGAN BEBERAPA PERLAKUAN PENDAHULUAN - Erynola Moniharapon; Sandra J Nendissa; Dina Laiyan (AGRITEKNO: Jurnal Teknologi Pertanian, 2017)
The objective of this study was to characterize the chemical properties of ‘lawa merah’ bean (Phaseolus vulgaris L.) with some pre-treatment. This study used a Complete Randomized Design with one factor which consisted of four treatment levels as follows: A0 (without pre-treatment), A1 (roasting for 20 minutes), A2 (boiling for 10 minutes) and A3 (roasting for 20 minutes and steaming for 30 minutes). The results showed that the best pre-treatment was A1 (roasting for 20 minutes), which produced ‘lawa merah’ bean flour with moisture content 7.81%, ash content of 2.92%, protein content of 26.75%, fat content of 2.15%, carbohydrate content of 5.92% and fiber content of 8.09%.